Cold temperature extremes during spring do not limit the range shift of Mediterranean pines into regions with intermittent frost. (3rd November 2015) - Bachofen, Christoph; Wohlgemuth, Thomas; Ghazoul, Jaboury; Moser, Barbara
Summary: Bioclimatic envelope models have predicted latitudinal range shifts of tree species in Europe following climate change. Accordingly, Mediterranean species will be able to migrate northwards if climatic conditions become warmer and dryer. Frost, on the other hand, is an important and recurring factor in temperate and boreal regions causing damage to buds and leaves, and potentially limiting the survival of Mediterranean tree species or populations at higher latitudes. Since species distribution models rely on average climatic parameters, they may underestimate the risk of frost damage from low temperature extremes. We measured the cold hardiness of Pinus sylvestris, Pinus nigra and Pinus halepensis seedlings from a total of 11 European populations growing in a common garden in a cold Central Alpine valley on seven dates between February and July 2013. On each date, needles were artificially frozen at several temperatures and the temperature estimated at which 50% of the needle tissue is damaged (LT50 ; relative electrolyte leakage). Cold hardiness did not differ between populations of the same species and was not related to the minimum temperatures at the seed origin. In comparison with deciduous trees, Mediterranean P. sylvestris and P. nigra maintained extremely wide safety margins against frost throughout late winter and spring. By contrast, safety margins of P. halepensis were much narrower until March and winter cold hardiness was in the range of regularly recurring low temperature events in Central Europe. According to the measured LT50 values, the migration of a wide range of drought‐tolerant populations of P. sylvestris and P. nigra from the Mediterranean to Central and Western Europe is not limited by intermittent cold temperature extremes in spring. They are notably as well adapted to frost as populations from Central Alpine origin. Differences in dehardening patterns between species demonstrate the importance of analysing cold hardiness repeatedly during potentially sensitive periods in order to predict species range shifts in the context of climatic change. Abstract : Lay Summary